Ctenodesma borneensis - Zieritz, Alexandra; Khairul Adha, Rahim (International Union for Conservation of Nature (IUCN), 2025)
Ctenodesma borneensis has most recently been assessed for The IUCN Red List of Threatened Species in 2024. Ctenodesma borneensis is listed as Endangered under criteria A2c.